Associations between peripheral artery disease and ischemic stroke: implications for primary and secondary prevention. - Banerjee, A; Fowkes, F; Rothwell, P (2010)
BACKGROUND AND PURPOSE: Although peripheral artery disease (PAD) has a particularly poor prognosis compared with vascular disease in other territories, little attention is paid to its epidemiology, treatment, and prevention. Despite the high prevalence of PAD in patients with stroke, and of stroke in patients with PAD, PAD is omitted from all guidelines for treatment, prevention, and rehabilitation of stroke, although coronary artery disease risk is considered. Therefore, routine PAD screening is seldom undertaken and so disease is probably often missed. Summary of Review- This review evaluates epidemiology of PAD in patients with stroke and of stroke in patients with PAD. The role of the ankle-brachial pressure index; imaging and novel markers in risk prediction of PAD in patients with stroke; and treatment and prevention of PAD are reviewed. CONCLUSIONS: In both primary and secondary prevention settings, PAD indicates a high risk of future events. Data on which additional preventive measures are beneficial in this patient group are lacking, but the presence of PAD does have implications for current management in both primary and secondary prevention of stroke.